STRATEGI PEMASARAN 4P: PRODUCT, PRICE, PLACE DAN PROMOTION PRODUK DEPOSITO PADA BAITUL MAAL WA TAMWIL DI PAYAKUMBUH - Lilly Kurnia; Zainuddin Zainuddin; Alimin Alimin (IAIN Batusangkar, 2021)
The problem in this article is how to apply the product, price, place, and promotion of deposit products at Baitul Maal wa Tamwil in Payakumbuh. The research uses qualitative methods and belongs to field research with semi-structured interviews and documentation as data collection techniques. The results of the findings show that BMT in Payakumbuh applies a marketing strategy (product) of deposit products carried out in the form of socialization to prospective customers and sending a letter of a deposit offer. Furthermore, the marketing strategy (price) is carried out by notifying the amount of ratio to be given on the nominal amount of deposits and providing convenience in the form of ball pick-up and giving deposit accounts to distant customers so as not to have to come to the office to deposit funds. The marketing strategy (place) of deposit products is to pay attention to the position of the BMT office to make it easier for customers to make transactions. Lastly, the marketing strategy (promotion) of deposit products on BMT is carried out with various advertisements in the form of brochures, letters of offer, and banners. Then BMT also promotes products through social media such as Facebook, Instagram, WhatsApp, and Twitter. In addition, BMT also uses sales promotion by giving gifts to customers for a number of funds and personal sales conducted by the marketing department in the form of direct socialization